PENDAMPINGAN PADA IBU HAMIL UNTUK MENIGKATKAN KADAR HEMOGLOBIN SEBAGAI UPAYA PENCEGAHAN ANEMIA PADA MASA KEHAMILAN - Susilia Idyawati; Baiq Ricca Afrida; Sri Hawari Jannati; Nina Zalfa Khairunnisa; Raudatul Jannah; Sri Handayani; Ni Putu Aryani (Institut Kesehatan Yarsi Mataram, 2026)
Anemia is one of the most common health problems affecting pregnant women and may lead to adverse maternal and fetal outcomes, including preterm birth, low birth weight, and increased maternal and neonatal morbidity and mortality. One of the government's strategies to prevent anemia is the provision of Iron and Folic Acid (IFA) tablets; however, adherence to IFA tablet consumption among pregnant women remains low. This community service program aimed to improve adherence to IFA tablet consumption and increase hemoglobin levels among pregnant women with anemia through a mentoring program. The intervention was conducted through home visits over a two-week period, including pre- and post-intervention hemoglobin assessment, education on anemia and the importance of IFA supplementation, nutritional counseling, and monitoring of IFA tablet consumption using an adherence checklist. The program involved seven pregnant women diagnosed with anemia in Lembar Selatan Village, West Lombok Regency. The results showed that six of the seven participants experienced an increase in hemoglobin levels after the mentoring program, while one participant showed a decrease due to family-related problems that affected adherence to IFA tablet consumption and adequate nutritional intake. The mentoring program also improved participants' understanding of anemia and the importance of regular IFA tablet consumption. In conclusion, home-based mentoring through education, counseling, and adherence monitoring was effective in improving hemoglobin levels among most pregnant women with anemia. Family involvement was identified as an important supporting factor for the success of the intervention..